Islamic home financing practices in selected OIC countries: an assessment in the light of Maqasid al-Shariah - Abdul Razak, Dzuljastri; Tazwar, Fahim (World Academy of Islamic Management (WAIM), 2018)
Home is one of the basic needs and an inborn dream for everyone. Home financing practiced by banks is a critical issue in meeting the objectives Maqasid Al-Shariah. The purpose of this study is to compare Islamic home financing practices adopted by banks in selected OIC countries namely Malaysia, Indonesia, Bangladesh and Syria and investigate the extent to which it has fulfilled these objectives and whether they are affordable. The methodology is by means of content analysis based on the literature review and library research. Although both conventional and Islamic housing schemes can provide assistance to people in acquiring their dream home, they are also subjected to high financing rates beyond the means of individuals. These practices bind the customers financially for long duration posing a burden that extends to the next generation. The result would assist Islamic banks towards improving the product features in terms of justice and fairness. It will also assist the governments and regulators to address the issue of affordability and high prices of houses especially in fulfilling the needs of the low-income household.